2011
DOI: 10.1186/1471-2407-11-102
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of SHOX2 Gene Amplification and DNA Methylation in Lung Cancer Tumors

Abstract: BackgroundDNA methylation in the SHOX2 locus was previously used to reliably detect lung cancer in a group of critical controls, including 'cytologically negative' samples with no visible tumor cell content, at a high specificity based on the analysis of bronchial lavage samples. This study aimed to investigate, if the methylation correlates with SHOX2 gene expression and/or copy number alterations. An amplification of the SHOX2 gene locus together with the observed tumor-specific hypermethylation might explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 39 publications
7
50
0
3
Order By: Relevance
“…The CE marked in vitro diagnostic test Epi proLung BL Reflex Assay is comprised of the three individual kits Epi proLung BL DNA Preparation Kit for the preparation of bisulfite converted DNA using ammonium bisulfite chemistry (15), the Epi proLung BL real-time PCR Kit for quantitative and sensitive determination of SHOX2 DNA methylation, and the Epi proLung BL Work Flow Control Kit for controlling the whole work flow.…”
Section: Patients Specimens and Model Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…The CE marked in vitro diagnostic test Epi proLung BL Reflex Assay is comprised of the three individual kits Epi proLung BL DNA Preparation Kit for the preparation of bisulfite converted DNA using ammonium bisulfite chemistry (15), the Epi proLung BL real-time PCR Kit for quantitative and sensitive determination of SHOX2 DNA methylation, and the Epi proLung BL Work Flow Control Kit for controlling the whole work flow.…”
Section: Patients Specimens and Model Samplesmentioning
confidence: 99%
“…Hypermethylation of the human homeobox gene SHOX2 (short stature homeobox 2) has previously been shown to be frequently accompanied by gene amplification (15). The positive performance of the SHOX2 DNA methylation biomarker in plasma could be due to a correlation of DNA methylation and locus amplification in malignant cells (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Увеличение числа копий гена SHOX2 было признано одним из самых распро-страненных и значимых хромосомных пере-строек при раке легкого [7][8][9][10][11]. В то же время, ненормальное метилирование гена SHOX2 является отличительной чертой раковых опухо-лей легких и коррелирует с увеличением числа копий участка локуса 3q25.3 [12,13].…”
Section: Introductionunclassified
“…The changes present in precancerous lesions [6] and some cancers [7] revealed that DNA methylation alterations play a key role in the early steps of human carcinogenesis. It has been a few decades now since Riggs, Holliday and Pugh proposed that DNA methylation was part of a system for controlling gene expression, and play an essential role in genome regulation, development and disease in mammalian cells [8,9]. Profiling of specific sites or panels of sites aberrantly methylated within tumor cells are currently being investigated as biomarkers for early prediction and prognostication, where cancer-associated methylation can be detected in tumor biopsy samples, cell-free serum, urine and peritoneal fluid [10][11][12].…”
Section: Introductionmentioning
confidence: 99%